Agricultural Credit Utilization and Repayment by Farm Households in Tripura - Ray, Poulami; Das, Bhagirath (Indian Journal of Extension Education, 2023)
The study was conducted in West Tripura district of Tripura to examine the utilization and repayment of farm loans obtained by borrowers based on a survey done in 2020.The development of agriculture depends on farmers receiving adequate and timely loans. Purposive multi-stage random sampling was used to pick 120 farmers and 20 lenders for a comprehensive investigation.The majority of the sample beneficiaries availed of crop loans (82.5%) as compared to allied activities loans (17.5%) and it was observed that marginal and small farmers diverted a portion of the loan as compared to medium farmers. The extent of repayment of loans by the medium farmers was higher than the small and marginal farmers. To improve the utilization and repayment pattern of credit by farm households, the Bank Field Officers need to conduct post-credit supervision to reduce credit diversion to unproductive uses and disbursement of the majority of the loan in kind form may be used.